A fatigue design concept for metal injection molded components of 100Cr6. Issue 2 (18th February 2015) - Lindel, H.; Hahn, M.; Bacher‐Höchst, M.; Issler, S.; Eifler, D.; Klein, M.; Baumgartner, Jörg
<x xml:space="preserve">Abstract</x> The fatigue behavior of rolled and machined high‐strength steel parts shows dependency on the size of material defects. In this work, the fatigue behavior of high‐strength steel specimens manufactured by Metal Injection Molding (MIM) process is investigated. Herein prealloyed 100Cr6 powder is used as base material and is sintered to 98.7% and to 95.2% relative density respectively. In order to avoid burrs resulting from the mold parting, an unconventional metal injection molding‐specific specimen shape is designed to perform experiments at notched and unmachined specimens, especially to assess the behavior of this material in component‐near conditions. Fatigue tests under axial loading with a load ratio of R = 0.1 were conducted with such specimens in martensitic condition. SEM analyses reveal that cracks originate from metal injection molding‐specific material discontinuities which can be seen as defects to this high strength steel. It was observed that irregularities at the surface, like surface roughness, open pores and locally melted surface areas lead to early fracture whereas defects in the volume, like non‐metallic inclusions lead to late fracture. Fracture mechanic analyses reveal that Murakami's short crack model is applicable to the 100Cr6 metal injection molding materials and therefore allows estimating the fatigue strength at N = 107 cycles of the metal injection molding‐material. Considering a weakest‐link approach, the fatigue strength at N = 107 cycles of the notched specimens can be well estimated using finite element modeling and the size distributions of the crack originating defects.